Website Based UI/UX Application Design of Balinese Traditional Products Using the Design Thinking Method - Narendra, Putu Riyaldi Putra; Ayu Wirdiani, Ni Kadek; Marini Mandenni, Ni Made Ika (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 11 No 2 (2023): Vol. 11, No. 2, August 2023DO - 10.24843/JIM.2023.v11.i02.p05, 2023)
Pandemic circumstances caused approximately 37.000 small and medium-sized enterprises or also known as (MSMEs) faced a decline. Employing technology can assist these businesses in marketing and selling their products beyond local boundaries, extending their reach to the national level. User Interface and User Experience market application for Balinese custom products as well as providing services related to Balinese custom. The Balinese Traditional Products marketplace application can provide products related to Balinese customs such as Hindu religious infrastructure, Balinese snacks, taru premana event organizer services, traditional massage services and others. The user interface and user experience designed using the Design Thinking method which produces a high fidelity prototype that can be tested like the final application. User experience development can be done as well as possible because development focuses on user needs. Through prototype testing using the usability testing method, the test results using System Usability Scale method get a score of 88.375. Based on these scores the designed prototype is included in the acceptable category in the acceptance rating, category B in the class scale and in the adjective ranking is included in the very good category.